Sustained inflammation 1.5 years post-stroke is not associated with depression in elderly stroke survivors - Noonan K (Dove Medical Press, 2013)
Kate Noonan,1,2 Sheila G Crewther,1,2 Leeanne M Carey,2,4 Michaela C Pascoe,5 Thomas Linden2,31School of Psychological Science, La Trobe University, Bundoora, Victoria, Australia; 2Florey Institute of Neuroscience and Mental Health, Melbourne Brain Centre, Heidelberg, Victoria, Australia; 3Institute of Neuroscience and Physiology, University of Gothenburg, Gothenburg, Sweden; 4Department of Occupational Therapy, School of Allied Health, La Trobe University, Bundoora, Victoria, Australia; 5Brain Sciences Institute, Swinburne University, Melbourne, AustraliaBackground: Depression is common in elderly stroke survivors and has been associated with systemic inflammation. We aimed to investigate an elderly population of Swedish stroke patients for evidence of sustained peripheral inflammation 18 months post-stroke and to identify if inflammation is associated with post-stroke depression at 18 months post-stroke.Methods: The Barthel Index was used to measure the level of impairment in activities of daily living at 3 days post-stroke. Serum concentrations of inflammation markers, ie, C-reactive protein and white cell count, were measured in 149 stroke patients (mean age 81 ± 5.33 years, 35% male) at 18 months post-stroke, and a comparison was made with an age-matched sample of elderly Swedish individuals who had not suffered a stroke. At the same visit, clinical depression was diagnosed according to the Diagnostic and Statistical Manual of Mental Disorders, Third Edition-Revised criteria. Severity of depression was assessed using the Montgomery-Asberg Depression Rating Scale (MADRS).Results: Mean C-reactive protein and white cell count levels in stroke patients were significantly elevated at 18 months post-stroke compared with population probands. Disability scores were associated with MADRS depression scores, but C-reactive protein and white cell count were not.Conclusion: We found evidence for a sustained peripheral inflammatory response at 18 months post-stroke. C-reactive protein and white cell count were not associated with depression in this study.Keywords: geriatric, inflammatory, ischemia, mood